2022
DOI: 10.3389/fmicb.2022.858036
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus delbrueckii CIDCA 133 Ameliorates Chemotherapy-Induced Mucositis by Modulating Epithelial Barrier and TLR2/4/Myd88/NF-κB Signaling Pathway

Abstract: Intestinal mucositis promoted by the use of anticancer drugs is characterized by ulcerative inflammation of the intestinal mucosa, a debilitating side effect in cancer patients undergoing treatment. Probiotics are a potential therapeutic option to alleviate intestinal mucositis due to their effects on epithelial barrier integrity and anti-inflammatory modulation. This study investigated the health-promoting impact of Lactobacillus delbrueckii CIDCA 133 in modulating inflammatory and epithelial barrier markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 67 publications
(114 reference statements)
4
11
1
Order By: Relevance
“…The reduction in mRNA expression of mucin 2 and tight junction proteins zonulin, claudin 1, and claudin 2 observed in the inflamed mice was attenuated by both heat-killed and cell-free supernatants of L. delbrueckii CIDCA 133. These results are consistent with data obtained by De Jesus et al [ 29 ] and Barroso et al [ 30 ], who demonstrated that viable L. delbrueckii CIDCA 133 reduced intestinal permeability and goblet cell degeneration and upregulated the gene expression of tight junction proteins ( Cldn1, Fr11, Hp ) altered by 5-FU chemotherapy, thus being essential to reduce the translocation of toxins and pathogenic bacteria, and consequently the inflammation amplification process in the intestinal mucosa [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The reduction in mRNA expression of mucin 2 and tight junction proteins zonulin, claudin 1, and claudin 2 observed in the inflamed mice was attenuated by both heat-killed and cell-free supernatants of L. delbrueckii CIDCA 133. These results are consistent with data obtained by De Jesus et al [ 29 ] and Barroso et al [ 30 ], who demonstrated that viable L. delbrueckii CIDCA 133 reduced intestinal permeability and goblet cell degeneration and upregulated the gene expression of tight junction proteins ( Cldn1, Fr11, Hp ) altered by 5-FU chemotherapy, thus being essential to reduce the translocation of toxins and pathogenic bacteria, and consequently the inflammation amplification process in the intestinal mucosa [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…The anti-inflammatory properties of viable L. delbrueckii CIDCA 133 have been previously reported [ 29 , 30 , 31 ]. This study evaluated the anti-inflammatory properties of the bacterial inactivation or secreted bioactive products derived from this strain in a 5-Fluorouracil drug-induced mouse intestinal inflammation model.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations